Sociotechnical Paradigm in the Study of Metadata Interoperability in Digital Libraries - Saputra, Dwi Fajar (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Metadata interoperability is a critical foundation for the effective development and management of digital libraries, enabling extensive, open, and sustainable access to information. Specific Background: Existing research predominantly adopts a positivistic paradigm, emphasizing technical conformity to metadata syntax, format validity, and interoperability protocols such as OAI-PMH and Dublin Core. Knowledge Gap: This technical focus often neglects social, semantic, and institutional contexts, resulting in limited adaptability to diverse user needs and institutional environments. Aims: This study introduces the sociotechnical paradigm as an alternative framework for understanding and enhancing metadata interoperability. Results: Through a literature review and reference to digital library development models, the research demonstrates how the sociotechnical paradigm integrates technological systems with social dynamics, institutional policies, and localized meaning-making processes. Novelty: The study reframes metadata interoperability not merely as a technical process but as a collaborative, participatory, and semantic negotiation among stakeholders. Implications: By embedding sociotechnical principles, digital libraries can evolve as adaptive socio-information systems that reflect user contexts, embrace diversity of meaning, and strengthen inclusivity in knowledge access. Highlights: Bridges technical and social dimensions of metadata. Promotes participatory and contextual design. Enhances inclusivity in digital library systems. Keywords: Metadata Interoperability, Sociotechnical Paradigm, Digital Libraries, Semantic Context, Inclusive Access